Comparison of photosynthetic responses between haptophyte Phaeocystis globosa and diatom Skeletonema costatum under phosphorus limitation - Chai, Xiaojie; Zheng, Lingling; Liu, Jin; Zhan, Jiao; Song, Lirong (Frontiers in Microbiology, 2023)
The diatom Skeletonema costatum and the haptophyte Phaeocystis globosa often form blooms in the coastal waters of the South China Sea. S. costatum commonly dominates in nutrient enrichment coastal waters, whereas P. globosa starts flourishing after the diatom blooms when phosphorus (P) is limited. Therefore, P limitation was proposed to be a critical factor affecting diatom–haptophyte transition. To elucidate the tolerance to P limitation in P. globosa compared with S. costatum, the effect of P limitation on their photosystem II (PSII) performance was investigated and their photosynthesis acclimation strategies in response to P limitation were evaluated. P limitation did not affect the growth of P. globosa over 7 days but decreased it for S. costatum. Correspondingly, the interiors and surrounding PSII of S. costatum were significantly inhibited by P limitation. The decline in PSII activity in S. costatum under P limitation was associated with the impairment of the oxygen-evolving complex (the donor side of PSII), the hindrance of electron transport from QA− to QB (the acceptor side of PSII), and the inhibition of electron transport to photosystem I (PSI). The 100% decrease in D1 protein level of S. costatum after P limitation for 6 days and PsbO protein level for 2 days was attributed to its enhanced photoinhibition. In contrast, P. globosa maintained its photosynthetic activity with minor impairment of the function of PSII compared with S. costatum. With accelerated PSII repair and highly increased non-photochemical quenching (NPQ), P. globosa can avoid serious PSII damage under P limitation. However, S. costatum decreased its D1 restoration under P limitation, and the maximum NPQ value in S. costatum was only one-sixth of that in P. globosa. A close interaction exists between the tolerance to P limitation and photosynthesis. These results provide additional evidence explaining how the different photosynthetic responses to P limitation in S. costatum and P. globosa effect their survival, dominance, and succession in natural environments